Anticancer Effects of Ethanolic Extracts of Macaranga Peltata Leaves on Human Oral Squamous Carcinoma Cell Lines: An In Vitro Study - Ravindran Rathy; Palani Jayanthi; Nripan T; Asha S. D; Pynadath Meera K (Wolters Kluwer Medknow Publications, 2024)
Cancer is a disease resulting from the disruption of cell cycle regulation, leading to the abnormal and unchecked proliferation of cells. Medicinal plants are rich in various bioactive phytochemicals or nutritional compounds. The aim is to determine the cytotoxic and genotoxic effects of ethanolic extracts of Macaranga peltata leaves on human oral cancer cell lines. The study setting was centre for Research on Molecular and Applied Sciences, Azeezia College of Dental Sciences and Research. The study design is a Comparative In Vitro study. Shade dried leaves of Macaranga peltata were subjected to Soxhlet extraction, and ethanolic extract was prepared. In vitro cytotoxic effects on human oral cancer cell lines were evaluated by (3-(4,5-dimethyl thiazole-2yl)-2,5-diphenyl tetrazolium bromide) MTT assay, and genotoxic effect was evaluated by comet assay. Untreated cell lines were used as control, and 5-fluorouracil was used as positive control. All experiments were performed in triplicates, and results were represented as Mean+/- SE. One-way ANOVA and Dunnet test were performed to analyze data. ***P < 0.001 compared with the control group. The ethanolic extract of Macaranga peltata exhibited cytotoxicity against oral cancer cells (LC50: 40.193089 μg/ml). There was a concentration-dependent increase in cell death, and at 100 μg/ml, the extract was most effective, causing 50% inhibition of viability. The comet assay showed significant genotoxic effects compared with 5-fluorouracil and untreated oral cancer cell lines. The ethanolic extract of Macaranga peltata leaves was subjected to MTT assay and comet using KB cell lines. The study concludes that the extract gave promising result for the anticancer activity on the KB cell lines producing cytotoxicity and genotoxicity.